A.A. Sakhno-Ustimovich and His Projects for Revival of Zaporozhye Cossacks under the Auspices of the White Movement - Anton A. Chemakin (RUDN Journal of Russian History)
The research is devoted to the activities of Colonel A.A. Sakhno-Ustimovich who served during the Civil War in the armies of the Ukrainian People's Republic, the Ukrainian State, and in the Armed Forces of South Russia. While serving in the White Army, he repeatedly proposed ideas for the revival of the Zaporozhye Cossacks. The aim of this study is to reconstruct Sakhno-Ustymovich's activities in reviving the Zaporozhye Cossacks. The source base is the materials from 6 archives, memoirs of contemporaries, and articles from emigrant periodicals (“Novoe Vremia,” “Ukrainska Trubuna,” and “Izvestiia Vysshego Monarkhicheskogo Soveta.” In the autumn of 1920, in Crimea, Sakhno-Ustymovich created the Orthodox Cossack Brotherhood which was supposed to become a kind of religious order and having secured support of a number of clerical hierarchy and atamans of the Cossack army, Sakhno-Ustimovich turned to P.N. Wrangel with a request to allow the formation of the “Camp of the Zaporozhye Cossack Army.” However, due to the evacuation of the Whites from Crimea, the project was never implemented. The author concludes that although Sakhno-Ustymovich was guided primarily by idealistic considerations, many of his supporters sought to preserve their privileged position through the revival of the Zaporozhye Cossacks.